Analysis of the Impact of Digital Marketing on Sales Growth of Lampung Tapis Handicraft MSMEs in the Digital Economy Era - Supri Yanto; Putri Irmala Sari; Nelly Suryani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was. This study aims to analyze the impact of digital marketing on the sales growth of Lampung Tapis handicraft micro, small, and medium enterprises (MSMEs) in the digital economy era. Despite the increasing adoption of digital marketing by traditional MSMEs, empirical evidence regarding its effectiveness in enhancing sales performance remains limited, particularly for culturally significant products such as Tapis handicrafts. Materials and methods. The study adopts a quantitative methodology, relying on primary data gathered via structured questionnaires administered to 50 Tapis MSME owners who are actively involved in digital marketing. Secondary sales data from the Cooperative and MSME Office of Lampung Province (2020–2023) further support the analysis. Statistical methods, including linear regression via SPSS, are applied to examine the relationship between digital marketing strategies. Results. The findings reveal a significant positive correlation between digital marketing adoption and sales growth, with a notable 35% average increase post implementation. Social media platforms, particularly Instagram and Facebook, emerge as the most influential drivers, outperforming marketplace based strategies. Key success factors include content creativity, customer engagement, and consistent promotional frequency. Conclusions. This study contributes to the digital marketing literature by validating the Technology Acceptance Model (TAM) in the context of traditional handicraft MSMEs, emphasizing the role of perceived usefulness and ease of use in technology adoption. Its originality lies in focusing on a culturally unique sector Lampung Tapis which has been underexplored in prior studies. Practical implications suggest the need for targeted government-led digital training programs and collaborations with local influencers to optimize MSMEs’ digital presence.